2020
DOI: 10.1111/jgs.16423
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Activities of Daily Living Independence and Mental Health Status Among Medicare Managed Care Patients

Abstract: BACKGROUND/OBJECTIVES Although there is a strong cross‐sectional association between dependence in activities of daily living (ADLs) and decreased mental health, it is largely unknown how the loss of specific ADLs, or the combination of ADLs, influences mental health outcomes. We examined the effect of ADL independence on mental health among participants in a large survey of Medicare managed care recipients. DESIGN/SETTING Retrospective cohort study. PARTICIPANTS A total of 104,716 participants in cohort 17 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Acceptance, support and understanding for the needs of the person with the LTC to shield/isolate supported coping, but participants also discussed challenges including their perceived loss of independence and reliance on others. Loss of independence was related to worsening mental health in a large longitudinal cohort prior to the pandemic [27] and considering the negative impact of loss of independence on mental and well-being is part of National Institute for Health and Care Excellence (NICE) guidance for working with older adults [28]. Considering how to balance the impact of loss of independence, whilst ensuring people with LTCs get the support they need when shielding/isolating is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance, support and understanding for the needs of the person with the LTC to shield/isolate supported coping, but participants also discussed challenges including their perceived loss of independence and reliance on others. Loss of independence was related to worsening mental health in a large longitudinal cohort prior to the pandemic [27] and considering the negative impact of loss of independence on mental and well-being is part of National Institute for Health and Care Excellence (NICE) guidance for working with older adults [28]. Considering how to balance the impact of loss of independence, whilst ensuring people with LTCs get the support they need when shielding/isolating is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvement of each of the functional outcomes showed correlation with improvement in pain catastrophizing, HADS anxiety, and HADS depression, our results demonstrate that improvement in HOOS ADL has the greatest magnitude of importance in the relationship with improvement in pain catastrophizing and HADS Depression/Anxiety. Loss of ADL independence has been shown to cause large declines in mental health, as functional impairment and pain have a strong impact on daily life, causing patients to avoid situations and activities that require the use of their problematic hip [44,45]. Conversely, it has been shown that relief from the factors that limit independence and social engagement can reduce feeling of helplessness and isolation, directly impacting feelings of depression and anxiety [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance, support and understanding for the needs of the person with the LTC to shield/isolate supported coping, but participants also discussed challenges including their perceived loss of independence and reliance on others. Loss of independence was related to worsening mental health in a large longitudinal cohort prior to the pandemic (Albanese et al, 2020) and considering the negative impact of loss of independence on mental and well-being is part of National Institute for Health and Care Excellence (NICE) guidance for working with older adults (NICE, 2015). Considering how to balance the impact of loss of independence, whilst ensuring people with LTCs get the support they need when shielding/isolating is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%